Ageing Characteristics of Stir Cast AZ 61 Alloy with Minor Additions - Tiwari, Amit; Kumar, Neeraj; Banerjee, M.K. (Recent Patents on Engineering, 2024)
Background: Knowing that magnesium (Mg) alloys and its composites bear the potential of being used simultaneously for light structural as well as biomedical applications, it appears prudent to look for developing a novel Mg alloy; the concurrent demand is to monitor recent trend in development of functional Mg-alloy and its composite materials through extensive patent search. Review of recent patents in the related field makes it relevant to investigate this aspect. Objective: The authors aim to study the evolution of structure and properties in stir cast of AZ- 61 alloy with minor additions of scandium, calcium and manganese. This paper reports the results of this investigation. Methods: The castings are prepared by stirring the molten alloy at 600 rpm for 10 minutes, followed by pouring into a preheated metal mould. The solidified alloys are homogenized at 550°C for 12 hours. The homogenized alloys are then subjected to solutionising treatment at 500°C for 5 hours; subsequently, the alloys are quenched in iced water. The quenched alloys are subjected to ageing treatment at different temperatures between 100°C to 400°C at an interval of 100°C. Similar experiments are conducted with its statically cast counterparts. The structure and properties of all the samples have been characterized by optical and scanning electron microscopy, and XRD analysis; DSC heating run is conducted to study the kinetics of phase transformation. Mechanical behaviour of castings is studied with the aid of tensile testing and fractography. Moreover, tribological behaviour of alloys is assessed by wear testing with the help of pin on disc method. Results: The results show that the stir cast alloy produces a homogeneous structure with significant improvement in properties. The precipitates of Mg17Al12, Al Mn, Mg Zn2, Al2 Ca and Mg2 Ca are formed due to the ageing of both stir cast and statically cast alloy. It is found that the diffusion of Al in magnesium controls the precipitation process. The tribological properties are found to be satisfactory for the stir cast alloy. Conclusion: The modified AZ61 alloy with minor additives, achieves excellent structural homogeneity and mechanical properties after stir casting followed by quench ageing.
Keywords: precipitation hardening